Environmental Impact of Fashion - Sharma, Mrs. Madhu (International Journal on Orange Technologies, 2023)
The fashion industry represent an important part of our economies, with a value of more than 2.5 trillion $USD and employing over 75 million people worldwide. The sector has seen spectacular growth over the past decades, as clothing production doubled between 2000 and 2014. While people bought 60% more garments in 2014 than in 2000, they only kept the clothes for half as long. While the fashion sector is booming, increasing attention has been brought to the impressive range of negative environmental impacts that the industry is responsible for. Fashion production makes up 10% of humanity’s carbon emissions, dries up water sources, and pollutes rivers and streams. What’s more, 85% of all textiles go to the dump each year. Fast fashion also has a human cost: textile workers, primarly women in developing countries, are often paid derisory wages and forced to work long hours in appalling conditions .In many places, these conditions create infringements on human rights (Human Rights Watch). Use of chemicals in clothes production also raise serious health concerns, both for the workers in the industry and consumers. Additional impacts on health also arise from the pollution described previously.